ANALISIS PENGARUH BRAND IMAGE DAN FASILITAS RUMAH SAKIT TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA KESEHATAN (Survey Pada RSI PKU Muhammadiyah Kabupaten Tegal) - Miftakhul Ulum; Hamidah Tussifah (Islamic Business and Management Journal, 2019)
Along with the development of increasingly sophisticated science and technology, hospitals as one of the providers of health services have a very important role in efforts to improve health services, both from the facilities they provide and the quality of services by creating excellence in terms of service quality, facilities, innovation and speed in responding to patient needs. This study aims to analyze the influence of brand image and facilities on consumer decisions using the health services of PKU Muhammadiyah Tegal Islamic Hospital. This type of research is quantitative and sampling uses Non-probability sampling with Purposive Sampling techniques with the number of respondents determined as many as 100 respondents. The analysis technique used is multiple linear regression analysis techniques. Data obtained through respondents with surveys in the form of questionnaires and measured using a Likert scale. The results showed that brand image did not have a positive and significant effect on decision making. While facilities have a positive and significant effect on decision making. Suggestions that can be conveyed related to the results of this study are as follows (1) to PKU Muhammadiyah Hospital in Kab. Tegal should always maintain and enhance factors that have a positive effect on decision making. (2) Evaluating factors that do not have a positive effect on decision making.